s+(-20)=-19

Simple and best practice solution for s+(-20)=-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s+(-20)=-19 equation:


Simplifying
s + (-20) = -19
s + -20 = -19

Reorder the terms:
-20 + s = -19

Solving
-20 + s = -19

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + s = -19 + 20

Combine like terms: -20 + 20 = 0
0 + s = -19 + 20
s = -19 + 20

Combine like terms: -19 + 20 = 1
s = 1

Simplifying
s = 1

See similar equations:

| -36y=4 | | 28=19-y | | (X-10)+(2x+40)=90 | | -7+7(6n-1)=-3n-14 | | 16x^2+3x+9=0 | | 2+19=-3(5x-7) | | 72x^2+81x=0 | | 0.4-0.28x=0.68x-2.48 | | sqrt(6x+7)-2=sqrt(2x+3) | | 8c^2-4-31c= | | 37.22=7g+3.83 | | 2(3x+5)=-34+2 | | 96=(2x+8)(2x+12)-96 | | -2X+31=2X+7 | | .25m-.33=.08333333333m+.33 | | (2x-4)(2x-4)=180 | | 24x^3y-68x^2y-56xy^3= | | 0.08x+0.09(9000-x)=780 | | 5x-3.4+4.2=4x-4.2 | | 1=(rx+sx)+t | | 2(3x+5)=4x-56 | | 24=-4(2x+6) | | 6x+19=4x+9 | | -10+3x=x | | x-11x=9 | | 1=(rx+six)+t | | 1.5x+50=1x+75 | | 2(-8)-3(4*-8+5)=-6(-8-3)-1 | | -4x-24=-10x+48 | | b=-36+7b | | 1+7v=6v-2 | | 44=6x+3x-5x+7x |

Equations solver categories